Selectivity of Entomopathogenic Fungi to Chrysoperla externa (Neuroptera: Chrysopidae) - Pamella Mingotti Dias; Elisângela de Souza Loureiro; Luis Gustavo Amorim Pessoa; Gabriel Luiz Reis Devoz; Gilson Bárbaro Barbosa Junior; Allan Macali Werner; Acacio Aparecido Navarrete; Paulo Eduardo Teodoro (Insects, 2020)
We aimed to evaluate the selectivity of entomopathogenic fungi to larvae of Chrysoperla externa (Neuroptera: Chrysopidae). For this purpose, Beauveria bassiana (strain ESALQ PL63), Metarhizium anisopliae (strain ESALQ E9) and Metarhizium rileyi (strain UFMS 03) were assessed at different concentrations (1 × 107, 1 × 108 and 1 × 109 conidia mL−1). The control treatment consisted of distilled water and Tween80 0.01. The treatments were applied with a Potter spray tower using two different methodologies: direct application (DA) and dry film (DF). Up to 96 h after application, no treatment provided a larval mortality above 3%. After 120 h, only B. bassiana induced significant mortality in all instars, with rates of 26%, 17% and 10% for first, second and third instar larval periods, respectively. There was no difference regarding to the application method or concentration of conidia. The percentage of individuals that revealed changes in the length of the larval and pupal periods varied among different treatments with entomopathogenic fungi and control treatments, application methodologies and concentrations. Despite B. bassiana revealing a higher mortality than M. anisopliae and M. rileyi on larvae of C. externa, these three entomopathogenic fungi may be used in association with C. externa for sustainable pest management.